Voices of the Far-Flung Areas: Experiences of Teachers Teaching in Remote Schools - Salazar, Edwin C.; Plaza, Christopher O. (Randwick International of Education and Linguistics Science Journal, 2025)
This study aimed to examine the insights, challenges and resiliency strategy of teachers teaching in the far-flung areas. The research employed the services of nine teacher-participants who qualified in the inclusion criteria such as serve in the locality for five years or more and must be a permanent teacher. Findings revealed that teachers face significant challenges including limited resources, difficult travel routes, and time management struggles. Despite these hurdles, they exhibit strong adaptability and resourcefulness, often relying on community engagement and personal resilience to navigate their demanding work environments. The study also highlights the crucial role of administrative support from the Department of Education in the form of professional development and resource augmentation—though many of these provisions fall short of lasting through the academic year. The research underscores the importance of enhancing existing DepEd policies, particularly in resource distribution, teacher localization, and sustained professional support. Additionally, community support emerged as a key factor influencing teacher retention, with those residing within their school’s community expressing a greater willingness to stay long-term. The findings advocate for a more inclusive, responsive, and sustainable approach to supporting teachers in remote areas to ensure equitable and quality education for all learners.